2021
DOI: 10.14710/jfma.v4i1.10106
|View full text |Cite
|
Sign up to set email alerts
|

REDUCING THE CLOCKWISE-ALGORITHM TO k LENGTH CLASSES

Abstract: In the present paper, we consider an optimization problem related to the extension in k-dimensions of the well known 3x3 points problem by Sam Loyd. In particular, thanks to a variation of the so called “clockwise-algorithm”, we show how it is possible to visit all the 3^k points of the k-dimensional grid given by the Cartesian product of (0, 1, 2) using covering trails formed by h(k)=(3^k-1)/2 links who belong to k (Euclidean) length classes. We can do this under the additional constraint of allowing only tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…would solve the aforementioned problem if only we could allow self-intersecting for those 6 links of prescribed length 1 + √ 2 units. Thanks to the MΛI-algorithm, we showed that it is possible to provide acceptable covering paths, inside the MAABB, whose edges belong to the same integer (and not only irrational [3]) length class, in two, three, and more dimensions. We hope that the arising questions concerning how many valid length classes there are for any k-tuple (n 1 , n 2 , .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…would solve the aforementioned problem if only we could allow self-intersecting for those 6 links of prescribed length 1 + √ 2 units. Thanks to the MΛI-algorithm, we showed that it is possible to provide acceptable covering paths, inside the MAABB, whose edges belong to the same integer (and not only irrational [3]) length class, in two, three, and more dimensions. We hope that the arising questions concerning how many valid length classes there are for any k-tuple (n 1 , n 2 , .…”
Section: Discussionmentioning
confidence: 99%
“…In Section 2, we also show how, for specific cases as n 1 = n k = 3, it is possible to shorten the link length [2] of the general solution provided by the MΛI-algorithm if we consider the bounding box k i=1 [0, n i ] (i.e., the RAABB) instead of the MAABB. Moreover, referring to the grid graphs G 3,3 = {0, 1, 2} × {0, 1, 2} and G 3,3,3 = {0, 1, 2} × {0, 1, 2} × {0, 1, 2}, we have constructively proved in [3] the existence of self-intersecting covering paths inside the MAABB (see Definition 1.3) that are formed by less than 3 k line segments, all belonging to the same irrational length class.…”
Section: E Regular Axis-aligned Bounding Box)mentioning
confidence: 94%
See 1 more Smart Citation
“…If k = 3, the best achievable sequence of knight jumps has length 24 (see [14], page 66, Figures 4&5). In addition, Figure 3 shows another polygonal chain, P (3, 3; {(1, 1, 1), (2, 0, 0)}) := (0, 0, 0) (3,4; {(1, 1, 1, 1)})∪{(0, 2, 0, 1) → (0, 0, 0, 2)} (see Figure 4), where P c (3, 4; {(1, 1, 1, 1)}) := (0, 0, 0, 2) → (2, 1, 0, 2) → (0, 2, 0, 2) →…”
mentioning
confidence: 99%